Systemic inflammation, innate immunity and pathogenesis after Zika virus infection in cynomolgus macaques are modulated by strain-specificity within the Asian lineage. Issue 1 (1st January 2021) - de Alwis, Ruklanthi; Zellweger, Raphaël M.; Chua, Edmond; Wang, Lin-Fa; Chawla, Tanu; Sessions, October M.; Marlier, Damien; Connolly, John E.; von Messling, Veronika; Anderson, Danielle E.
ABSTRACT: Zika virus (ZIKV) is an emerging arbovirus with recent global expansion. Historically, ZIKV infections with Asian lineages have been associated with mild disease such as rash and fever. However, recent Asian sub-lineages have caused outbreaks in the South Pacific and Latin America with increased prevalence of neurological disorders in infants and adults. Asian sub-lineage differences may partially explain the range of disease severity observed. However, the effect of Asian sub-lineage differences on pathogenesis remains poorly characterized. Current study conducts a head-to-head comparison of three Asian sub-lineages that are representative of the circulating ancestral mild Asian strain (ZIKV-SG), the 2007 epidemic French Polynesian strain (ZIKV-FP), and the 2013 epidemic Brazil strain (ZIKV-Brazil) in adult Cynomolgus macaques. Animals infected intervenously or subcutaneously with either of the three clinical isolates showed sub-lineage-specific differences in viral pathogenesis, early innate immune responses and systemic inflammation. Despite the lack of neurological symptoms in infected animals, the epidemiologically neurotropic ZIKV sub-lineages (ZIKV-Brazil and/or ZIKV-FP) were associated with more sustained viral replication, higher systemic inflammation (i.e. higher levels of TNFα, MCP-1, IL15 and G-CSF) and greater percentage of CD14+ monocytes and dendritic cells in blood. Multidimensional analysis showed clustering of ZIKV-SG away from ZIKV-Brazil and ZIKV-FP, further confirming sub-lineage differences in the measured parameters. These findings highlight greater systemic inflammation and monocyte recruitment as possible risk factors of adult ZIKV disease observed during the 2007 FP and 2013 Brazil epidemics. Future studies should explore the use of anti-inflammatory therapeutics as early treatment to prevent ZIKV-associated disease in adults.